Encarnación's kitchen : Mexican recipes from nineteenth-century California : selections from Encarnación Pinedo's El cocinero español - Pinedo, Encarnación, 1848- (California studies in food and culture ;, 2003)
In 1991 Ruth Reichl, then a Los Angeles Times food writer, observed that much of the style now identified with California cuisine, and with nouvelle cuisine du Mexique, was practiced by Encarnación Pinedo a century earlier. A landmark of American cuisine first published in 1898 as El cocinero español (The Spanish Cook), Encarnación's Kitchen is the first cookbook written by a Hispanic in the United States, as well as the first recording of Californio food-Mexican cuisine prepared by the Spanish-speaking peoples born in California. Pinedo's cookbook offers a fascinating look into the kitchens o.